Factors That Influence the Quality of RNA From the Pancreas of Organ Donors. Issue 2 (February 2017) - Philips, Tiffany; Kusmartseva, Irina; Gerling, Ivan C.; Campbell-Thompson, Martha; Wasserfall, Clive; Pugliese, Alberto; Longmate, Jeffrey A.; Schatz, Desmond A.; Atkinson, Mark A.; Kaddis, John S.
Abstract : Objectives: Attaining high-quality RNA from the tissues or organs of deceased donors used for research can be challenging due to physiological and logistical considerations. In this investigation, Methods: RNA Integrity Number (RIN) was determined in pancreatic samples from 236 organ donors and used to define high (≥6.5) and low (⩽4.5) quality RNAs. Logistic regression was used to evaluate the potential effects of novel or established organ and donor factors on RIN. Results: Univariate analysis revealed donor cause of death (odds ratio [OR], 0.35; 95% confidence interval [CI], 0.15–0.77; P = 0.01), prolonged tissue storage before RNA extraction (OR, 0.65; 95% CI, 0.52–0.79; P < 0.01), pancreas region sampled (multiple comparisons, P < 0.01), and sample type (OR, 0.32; 95% CI, 0.15–0.67; P < 0.01) negatively influenced outcome. Conversely, duration of final hospitalization (OR, 3.95; 95% CI, 1.59–10.37; P < 0.01) and sample collection protocol (OR, 8.48; 95% CI, 3.96–19.30; P < 0.01) positively impacted outcome. Islet RNA obtained via laser capture microdissection improved RIN when compared with total pancreatic RNA from the same donor (ΔRIN = 1.3; 95% CI, 0.6–2.0; P < 0.01). Conclusions: A multivariable model demonstrates that autopsy-free and biopsy-free human pancreata received, processed, and preserved at a single center, using optimized procedures, from organ donors dying of anoxia with normal lipase levels increase the odds of obtaining high-quality RNA. Abstract : Supplemental digital content is available in the text.